TOTAL HIP ARTHROPLASTY IN PATIENTS WITH JUVENILE ARTHRITIS - D. V. Ivanov; S. A. Makarov; D. E. Karateev; V. P. Pavlov; M. A. Makarov; A. L. Logunov; I. P. Nikishina; T. A. Shelepina; V. N. Amirdzhanova (Научно-практическая ревматология)
Prolonged hip arthritis in juvenile arthritis (JA) is a cause of serious joint destruction, leading to severe pain and functional disorders.Objective: to assess the results of total hip arthroplasty (THA) in patients with JA. Subjects and methods. The investigation enrolled 20 women and 2 men. Their mean age at the time of surgery was 27.9 (18–49) years, mean weight – 47.7±2 kg. Mean height was 155.1 cm, which confirms growth retardation in these patients. The disease duration averaged 7.1 years. Mild protrusion of the acetabulum was stated in 9 (41%) and 13 (59%) patients, respectively.Results and discussion. Functional status was assessed with Harris hip score (HHS), and Health Assessment Questionnaire (HAQ), pain – with visual analogue scale (VAS) quality of life (QL) – with EQ-5D before and 6–12 months after surgery. Six months after surgery, the mean EQ-5D score increased from 0.13 to 0.47 (ΔEQ-5D = 0.34;р< 0.05), which corresponded to a moderate clinical response in QL. Only after 12 months of follow-up, there was a pronounced effect of surgical treatment: the EQ-5D index increased up to 0.64 (ΔEQ-5D = 0.51; p< 0.05). On the average, HAQ decreased from 2.016 to 1.429 after 6 months and to 1.159 after 12 months, which was suggestive of a significant clinical improvement. Functional status also improved according to HHS: at 6 months, it was assessed as good (HHS, 80-89) in 3 (13.6%) patients; satisfactory – in 9 (40.9%), and 10 (45.5%) patients had HHS below 70; at 12 months, it was excellent (HHS, 90–100) in 4 (18.2%), good (80–89) – in 4 (18.2%), satisfactory – in 8 (36.4%) and 6 (27.2%) patients had HHS lower than 70. Preoperatively, pain on VAS averaged 65.4 mm; 6 and 12 months following surgery, it reduced to 41.6 and 36.3 mm, respectively. Conclusion. THA in patients with JA significantly improves the function of the affected hip joint and QL. It is also important to note that THA promotes social adaptation – three patients have entered higher educational establishments and two more patients have got married and given birth to healthy babies.